Phosphatidylinositol‐3‐phosphate in the regulation of autophagy membrane dynamics. (5th January 2017) - Nascimbeni, Anna Chiara; Codogno, Patrice; Morel, Etienne
Abstract : Phosphatidylinositol‐3‐phosphate (PI3P) is a key player in membrane dynamics and trafficking regulation. Most PI3P is associated with endosomal membranes and with the autophagosome preassembly machinery, presumably at the endoplasmic reticulum. The enzyme responsible for most PI3P synthesis, VPS34 and proteins such as Beclin1 and ATG14L that regulate PI3P levels are positive modulators of autophagy initiation. It had been assumed that a local PI3P pool was present at autophagosomes and preautophagosomal structures, such as the omegasome and the phagophore. This was recently confirmed by the demonstration that PI3P‐binding proteins participate in the complex sequence of signalling that results in autophagosome assembly and activity. Here we summarize the historical discoveries of PI3P lipid kinase involvement in autophagy, and we discuss the proposed role of PI3P during autophagy, notably during the autophagosome biogenesis sequence. Abstract : Autophagy is the major conserved catabolic pathway and plays a fundamental role in cell physiology and pathophysiology. The biogenesis of the autophagosome is complex and still incompletely understood. It requires the recruitment and coordination of multiple protein complexes and several membrane dynamics events. Phosphatidylinositol‐3‐phosphate (PI3P) is emerging as a crucial actor of autophagy and here we discuss its proposed role during the different steps of the autophagosome biogenesis sequence.